Removal of Staphylococcus aureus using electro-fenton, UV/H2O2, and combination of electro-fenton and UV/H2O2 processes; optimization of operational parameters - Asiyeh Dokhani; Babak kheirkhah; Davood Kalantar-Neyestanaki; Farokh Rokhbakhsh-Zamin; Maryam Dolatabadi; Saeid Ahmadzadeh (Applied Water Science, 2024)
Abstract Staphylococcus aureus (S. aureus) is an opportunistic pathogen of the gram-positive variety, known to cause a range of severe infections including cellulitis, pneumonia, osteomyelitis, endocarditis, and sepsis. These infections are associated with significant morbidity and mortality rates in both hospital and community settings. Therefore, it is important to remove S. aureus from the aqueous solution. The present study employed response surface methodology as an effective strategy to optimize the removal of S. aureus through the electro-Fenton (EF), UV/H2O2, and combination EF-UV/H2O2 processes. Under the optimized conditions, the maximum removal efficiency in the EF process of 48.5%, UV/H2O2 process of 36.2%, and combination EF-UV/H2O2 process of 100%. The optimum condition for removal efficiency using combination EF-UV/H2O2 process of 100% was attained at S. aureus concentration of 5 × 106 CFU mL−1, current density of 8.0 mA cm−2, H2O2 dosage of 170 µL L−1, and 2 lamps UV during 7.0 min. Both the production of •OH in the EF and UV/H2O2 process and the additive oxidation effect of UV/H2O2 are the main reasons for the better performance of combination EF-UV/H2O2 process. The results indicate that the EF-UV/H2O2 process is highly promising and environmentally sustainable method for treating wastewater samples contaminated with S. aureus.